1994
DOI: 10.1073/pnas.91.1.281
|View full text |Cite
|
Sign up to set email alerts
|

Variable thermal emission and chlorophyll fluorescence in photosystem II particles.

Abstract: In photosynthetic systems, the absorbed light energy is used to generate electron transport or it is lost in the form of fluorescence and thermal emission. While fluorescence can be readily measured, the detection of thermal deactivation processes can be achieved by the photoacoustic technique. In that case, the pressure wave generated by the thermal deactivations in a sample irradiated with modulated light is detected by a sensitive microphone. The relationships between the yield of fluorescence and thermal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Finally, P680 + is a strong quencher of Chl a fluorescence (Steffen et al 2005) and this effect allows the study of the different redox states (S states) the oxygen-evolving complex of PSII, due to the fact that the lifetime of P680 + is S state dependent. All of these things taken together could turn Chl a fluorescence into a indecipherable signal, but thanks to the development of specific protocols, and by using complementary techniques, the different effects can be separated, turning Chl a fluorescence into a powerful tool for the study of photosynthesis: quenching analysis (Bradbury and Baker 1981; Quick and Horton 1984; Schreiber et al 1986), JIP test (Strasser and Strasser 1995; Strasser et al 2004), non-photochemical quenching (NPQ) (Demmig and Winter 1988; Horton and Hague 1988), electron transport rate (ETR) (Genty et al 1989; Krall and Edwards 1990), rapid light curves (RLCs) (White and Critchley 1999; Ralph and Gademann 2005), flash-induced fluorescence (Robinson and Crofts 1983; de Wijn and van Gorkom 2001; Bouges-Bocquet 1980, Ioannidis et al 2000), dark-adaptation kinetics of OJIP transients (Bukhov et al 2001; Schansker et al 2005), Chl a fluorescence and photoacoustic spectroscopy (Buschmann and Koscányi 1989; Snel et al 1990; Allakhverdiev et al 1994; Bukhov et al 1997), Chl a fluorescence and 820-nm absorbance/transmission (Klughammer and Schreiber 1994; Schansker et al 2003), Chl a fluorescence and delayed fluorescence (Goltsev et al 2012; Kalaji et al 2012a), imaging (Nedbal and Whitmarsh 2004; Hideg and Schreiber 2007; Lichtenthaler et al 2007; Gorbe and Calatayud 2012), the actinic light wavelength dependence of photosynthesis (Schreiber et al 2012) and more recently attention has been paid to statistic aspects of the measurements of parameters (e.g., Bussotti et al 2011a). The photosynthetic literature is huge with many topics studied such as plant breeding (Baker and Rosenqvist 2004; Kalaji and Pietkiewicz 2004; Kalaji and Guo 2008), seed vigor and seed quality assessment (Jalink et al 1998; Dell’Aquila et al 2002; Konstantinova et al 2002), fruit and vegetable quality determination and postharvest processing control (Merz et al 1996; Nedbal et al 2000), senescence (Adams et al 1990a; Kotakis et al 2014), climate change effects (Ashraf and Harris 2004) and a variety of algae (Gorbunov et al 1999; Antal et al …”
Section: Question 1: What Is Chlorophyll a Fluorescence And Why Do Wementioning
confidence: 99%
“…Finally, P680 + is a strong quencher of Chl a fluorescence (Steffen et al 2005) and this effect allows the study of the different redox states (S states) the oxygen-evolving complex of PSII, due to the fact that the lifetime of P680 + is S state dependent. All of these things taken together could turn Chl a fluorescence into a indecipherable signal, but thanks to the development of specific protocols, and by using complementary techniques, the different effects can be separated, turning Chl a fluorescence into a powerful tool for the study of photosynthesis: quenching analysis (Bradbury and Baker 1981; Quick and Horton 1984; Schreiber et al 1986), JIP test (Strasser and Strasser 1995; Strasser et al 2004), non-photochemical quenching (NPQ) (Demmig and Winter 1988; Horton and Hague 1988), electron transport rate (ETR) (Genty et al 1989; Krall and Edwards 1990), rapid light curves (RLCs) (White and Critchley 1999; Ralph and Gademann 2005), flash-induced fluorescence (Robinson and Crofts 1983; de Wijn and van Gorkom 2001; Bouges-Bocquet 1980, Ioannidis et al 2000), dark-adaptation kinetics of OJIP transients (Bukhov et al 2001; Schansker et al 2005), Chl a fluorescence and photoacoustic spectroscopy (Buschmann and Koscányi 1989; Snel et al 1990; Allakhverdiev et al 1994; Bukhov et al 1997), Chl a fluorescence and 820-nm absorbance/transmission (Klughammer and Schreiber 1994; Schansker et al 2003), Chl a fluorescence and delayed fluorescence (Goltsev et al 2012; Kalaji et al 2012a), imaging (Nedbal and Whitmarsh 2004; Hideg and Schreiber 2007; Lichtenthaler et al 2007; Gorbe and Calatayud 2012), the actinic light wavelength dependence of photosynthesis (Schreiber et al 2012) and more recently attention has been paid to statistic aspects of the measurements of parameters (e.g., Bussotti et al 2011a). The photosynthetic literature is huge with many topics studied such as plant breeding (Baker and Rosenqvist 2004; Kalaji and Pietkiewicz 2004; Kalaji and Guo 2008), seed vigor and seed quality assessment (Jalink et al 1998; Dell’Aquila et al 2002; Konstantinova et al 2002), fruit and vegetable quality determination and postharvest processing control (Merz et al 1996; Nedbal et al 2000), senescence (Adams et al 1990a; Kotakis et al 2014), climate change effects (Ashraf and Harris 2004) and a variety of algae (Gorbunov et al 1999; Antal et al …”
Section: Question 1: What Is Chlorophyll a Fluorescence And Why Do Wementioning
confidence: 99%
“…The photoacoustic-measuring beam was provided from a 150 W xenon lamp (ILC Technology, Sunnydale, CA) as reported (45)(46)(47). The intensity of this measuring beam (680 nm, 35 Hz) was 3 W m-2.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneous fluorescence and photoacoustic measurements were performed using a laboratory-constructed instrument composed of a photoacoustic cell (MTEC Photoacoustics Inc., Ames, IA) in combination with a PAM-101 chlorophyll fluorometer (Walz, Effeltrich, Germany) as previously described (45). The photoacoustic-measuring beam was provided from a 150 W xenon lamp (ILC Technology, Sunnydale, CA) as reported (45)(46)(47).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, numerous studies have revealed strong correlations between the kinetic and magnitude of both signals (for examples see Havaux 1988;Allakhverdiev et al 1994;Markovic and Carpentier 1995). In dark-adapted intact leaves, the fast increase in chlorophyll fluorescence that follows the onset of actinic light was found to proceed simultaneously with a decline in the 0,-dependent component of the PA signal (Malkin 1987;Havaux 1988;Vredenberg et al 1992).…”
Section: Introductionmentioning
confidence: 95%